Well, your question is basically;
x²+6x+5
Well first you have to find two numbers that when added will give you +6 and when multiplied will give you 5. Well, in this case, the numbers are; (+1 and +5). So you add them to the equation. So;
x²+1x+5x+5
Hope you noticed that 6x was removed. Anyway;
You have to put the equation in two brackets with two terms in each
(x²+1x)+(5x+5)
Next, you bring out what is commom in each bracket and use it to divide what is in the bracket
x(x+1)+5(x+1)
Now you notice that the two things in the bracket are the same. They have to be.
Next, you put the terms outside the bracket together and choose one of the terms in a bracket. So;
(x+5) (x+1)
So the equation factorised is (x+5) (x+1). But if you want to go ahead to find x, then you can say;
(x+5) (x+1)
x+5=0 x+1=0
Take the +5 over Take the +1 over the equal to, where it becomes -1. So;
the equal sign where x=-1
it becomes -5. So;
x=-5 OR x=-1
By the way, here's a little secret, the answers are always the opposite of the two numbers chosen at the beginning(+1 and +5). Hope i helped. If you have any more problems, let me know.
Answer:
need please
Step-by-step explanation:
it's for today please help me
Answer:
Press A takes 10 hours to do a certain job. So Press A does (1/10)th of the job in an hour.
Press A and Press B, together do (1/2.5) or (4/10)th of the job in an hour.
So Press B does (4/10)-(1/10) = (3/10)th of the job in an hour. So Press B can do the job in (10/3) hours or 3 hour and 20 mins.
Check: A does (1/10)th and B does (3/10)th part of the job in an hour. A and B together will take (1/10)+(3/10) = 4/10th of the job in an hour. So they will complete the job in 10/4 = 2.5 hours. Correct.
Answer: Press B can do the job in 3 hour and 20 mins.
Step-by-step explanation:
Answer:
x = 2 csc(1) y - π/4
Step-by-step explanation:
Solve for x:
y = 1/2 sin(1) (x + π/4)
y = 1/2 (x + π/4) sin(1) is equivalent to 1/2 (x + π/4) sin(1) = y:
1/2 sin(1) (x + π/4) = y
Divide both sides by sin(1)/2:
x + π/4 = 2 csc(1) y
Subtract π/4 from both sides:
Answer: x = 2 csc(1) y - π/4